COLLECTION OF STORIES BY FEDOR DUDKA "SNOW-STORM": IDEOLOGICAL-THEMATIC AND GENRE-STYLISH ASPECTS - Komyshyn, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
High-thematic and genre-stylish peculiarities of F. Dydko’s collection “Blizzard” has been analysed in the article. It has been proved , that romantic sensation of the world is dominating here and it is displayed in the texts as the implementation of aesthetics and poetics elements of romanticism and shows the effect oh the individual-suggestive factor. The thematic range of the collection has found its personification in the genres of the narrative and classic short story (the subject of unhappy love that it is transformed into the motif of the eternal world beaty, woman’s beaty, people’s harmony with the nature, even the subject of the liberation movement, within the limits of which the motif of destiny is realized).